Digital Communication Strategies in Supporting Organizational Transformation in the 4.0 Era at the Religious Training Center of Denpasar - Suparna, Putu (Doctoral Program of Social Science Pasundan University, 2024)
The Industrial Revolution 4.0 era has brought significant changes across various aspects, including organizational communication. Organizational transformation has become essential to address the challenges and opportunities emerging in the digital age. This study aims to analyze the digital communication strategies implemented by the Balai Diklat Keagamaan Denpasar (Religious Training Center of Denpasar) to support organizational transformation. Using a qualitative approach, the research employs a case study method to explore the implementation of digital communication in enhancing organizational effectiveness. Data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that integrated digital communication strategies, such as utilizing social media, technology-based applications, and relevant digital content management, play a pivotal role in improving internal and external communication efficiency. Additionally, these strategies foster collaboration, adaptation to changes, and the establishment of a technology-driven work culture. However, the study also identifies challenges, such as technological infrastructure limitations and low digital literacy among employees. Therefore, continuous digital literacy training and increased investment in technological infrastructure are recommended to sustain organizational transformation. This study provides valuable insights for other organizations aiming to implement digital communication strategies to address the challenges of the 4.0 era.